2014
DOI: 10.1039/c4cc02225d
|View full text |Cite
|
Sign up to set email alerts
|

B182−: a quasi-planar bowl member of the Wankel motor family

Abstract: A quasi-planar member of the so-called 'Wankel motor' family, B18(2-), is found. This boron cluster is an electronically stable dianion and a concentric doubly σ- and π-aromatic system. The inner B6 unit in B18(2-) undergoes quasi-free rotation inside the perimeter of the B12 ring. The absence of any localized σ-bond between the inner ring and the peripheral boron atoms makes the system fluxional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 29 publications
3
78
1
Order By: Relevance
“…[16][17][18][19] This has recently been rationalized by aromaticity arguments and has stressed the importance of non-polyhedral boron frameworks. [20][21][22] Thus, when a fully substituted dodecaborate is stripped from its substituents step by step, it must pass a degree of substitution where the closed icosahedral structure opens. For the partially hydrogenated borates B 12 H nˉ and B 6 H nˉ a 3D to 2D transition is predicted in-between n=4 and n=3.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] This has recently been rationalized by aromaticity arguments and has stressed the importance of non-polyhedral boron frameworks. [20][21][22] Thus, when a fully substituted dodecaborate is stripped from its substituents step by step, it must pass a degree of substitution where the closed icosahedral structure opens. For the partially hydrogenated borates B 12 H nˉ and B 6 H nˉ a 3D to 2D transition is predicted in-between n=4 and n=3.…”
Section: Introductionmentioning
confidence: 99%
“…18,[27][28][29][30][31][32] first-principles methods. [28][29][30][31][32] In particular, first-principles molecular dynamics (FPMD) simulations demonstrated that the structural transformation of B 5 fragment between six-and seven-membered rings is an element process in isomerization of the B 40 fullerene. 18 The axially chiral B 39 − fullerenes possess a distinctive structural fluxionality: B 39 − hops between the C 3 and C 2 isomers with low energy barriers during FPMD simulations at 300K.…”
Section: -9mentioning
confidence: 99%
“…Boron-based nanoclusters are af ertile ground for unique quasi-planar (2D) structures up to 40 atoms, [1][2][3][4][5][6] extreme coordination environments, [1] and intriguing dynamic properties; [7][8][9][10][11][12][13][14][15][16][17] all these phenomena are attributed to the electron deficiencyo fb oron. During the past decades,n anomachines (including molecular rotors) [18] have emerged as ahot topic in chemistry and nanoscience.Aspectroscopic study of Zhai, Wang, and Boldyrev in 2010 on a2Dwheel-like B 19 À cluster [4] sparked an immediate proposal of molecular Wankel motor by Merino,Heine,and co-workers, [7] which was subsequently extended to aseries of circular clusters:B 13 + ,B 18 2À ,B 20 2À ,and B 12 Ir À .…”
mentioning
confidence: 99%
“…During the past decades,n anomachines (including molecular rotors) [18] have emerged as ahot topic in chemistry and nanoscience.Aspectroscopic study of Zhai, Wang, and Boldyrev in 2010 on a2Dwheel-like B 19 À cluster [4] sparked an immediate proposal of molecular Wankel motor by Merino,Heine,and co-workers, [7] which was subsequently extended to aseries of circular clusters:B 13 + ,B 18 2À ,B 20 2À ,and B 12 Ir À . [8][9][10][11][12][13][14] Elongated boron clusters (B 11 ,B 11 À ,a nd B 15 + )…”
mentioning
confidence: 99%